COVID‐19 vaccine research and development: ethical issues - Wibawa, T. (Tropical medicine & international health, 2021)
The achievements of vaccine research and development bring a hope to our societies that we may cope with the COVID‐19 pandemic. There are two aspects that should be maintained in balance: the immediate necessity for speed of vaccine research and the inherent need for protection of research subjects, which is the foremost concern of research ethics. This narrative review highlights ethical issues in COVID‐19 vaccine research and development that every stakeholder needs to be aware of and to consider.